A pyrene-appended spiropyran for selective photo-switchable binding of Zn(II): UV–visible and fluorescence spectroscopy studies of binding and non-covalent attachment to graphene, graphene oxide and carbon nanotubes. Issue 38 (23rd September 2015) - Perry, Alexis; Green, Stephen J.; Horsell, David W.; Hornett, Sam M.; Wood, Mark E.
Abstract: Synthesis of photo-switchable, Zn 2+ sensitive hybrid materials was achieved by facile non-covalent functionalization of graphene, graphene oxide and carbon nanotubes with a pyrene-appended spiropyran. Solution phase binding studies, using UV–visible and fluorescence spectroscopy, indicated that the pyrene-spiropyran dyad was highly selective for Zn 2+ over a range of potentially competitive cations and that binding occurred with 1:1 stoichiometry and a binding constant of K =1.4×10 4 mol −1 dm 3 at 295 K. Zn 2+ binding was promoted by UV irradiation or in darkness and reversed upon irradiation with visible light. Graphical abstract: